The impact of social structure and dynamics on the evolution of language in the Jaffna peninsula - T.Arunakirinathan (Book of Abstracts, Annual Research Symposium 2014, 2014)
The culture, language and psychological processes of human beings are inseparably interwoven and often contribute to each other. The societies existing in relative isolation would be ideal to ascertain this fact. The population of Jaffna peninsula, the Northern most part of Sri Lanka was relatively isolated due to the geographical location and due to socio-political and cultural reasons for several centuries. Further a monolingual situation prevails there and the population consists of mostly ethnic Tamils. Thus it fulfills the necessary conditions to initiate this study.